Body mass index and outcome after revascularization for symptomatic carotid artery stenosis - Volkers, Eline J.; Ringleb, Peter A. (Neurology, 2017)
Objective: To determine whether the obesity paradox exists in patients who undergo carotid artery stenting (CAS) or carotid endarterectomy (CEA) for symptomatic carotid artery stenosis. Methods: We combined individual patient data from 2 randomized trials (Endarterectomy vs Angioplasty in Patients with Symptomatic Severe Carotid Stenosis and Stent-Protected Angioplasty vs Carotid Endarterectomy) and 3 centers in a third trial (International Carotid Stenting Study). Baseline body mass index (BMI) was available for 1,969 patients and classified into 4 groups: <20, 20-<25, 25-<30, and ≥30 kg/m2. Primary outcome was stroke or death, investigated separately for the periprocedural and postprocedural period (≤120 days/>120 days after randomization). This outcome was compared between different BMI strata in CAS and CEA patients separately, and in the total group. We performed intention-to-treat multivariable Cox regression analyses. Results: Median follow-up was 2.0 years. Stroke or death occurred in 159 patients in the periprocedural (cumulative risk 8.1%) and in 270 patients in the postprocedural period (rate 4.8/100 person-years). BMI did not affect periprocedural risk of stroke or death for patients assigned to CAS (ptrend = 0.39) or CEA (ptrend = 0.77) or for the total group (ptrend = 0.48). Within the total group, patients with BMI 25-<30 had lower postprocedural risk of stroke or death than patients with BMI 20-<25 (BMI 25-<30 vs BMI 20-<25; hazard ratio 0.72; 95% confidence interval 0.55-0.94). Conclusions: BMI is not associated with periprocedural risk of stroke or death; however, BMI 25-<30 is associated with lower postprocedural risk than BMI 20-<25. These observations were similar for CAS and CEA.